An Overview on Medicinal Chemistry of Synthetic and Natural Derivatives of Cannabidiol - Morales, Paula; Reggio, Patricia H.; Jagerovic, Nadine (Frontiers in Pharmacology, 2017)
Cannabidiol (CBD) has been traditionally used in Cannabis-based preparation, however historically it has received far less interest as a single drug than the other components of Cannabis. Currently, CBD generates considerable interest due to its beneficial neuroprotective, antiepileptic, anxiolytic, antipsychotic, and anti-inflammatory properties. Therefore, the CBD scaffold becomes of increasing interest for medicinal chemists. This review provides an overview of the chemical structure of natural and synthetic CBD derivatives including the molecular targets associated with these compounds. A clear identification of their biological targets has been shown to be still very challenging.